Magical and Mystical Aspects in Nepali Manuscript Illuminations - Sharma, Yam Prasad (Curriculum Development Journal, 2021)
Nepali Manuscript illuminations are traditional miniature paintings found in religious manuscripts, including Prajnaparamita, Pancaraksa, Shivadharma, Visnudharma, and Devimahatmya. The religious manuscripts narrate mythical events in verbal texts and illustrate mythical characters and their actions simultaneously. The forms, figures and activities of the characters are symbolic, magical and mystical. The paintings present divine and supernatural characters in their spectacular feats of real life. The artworks represent the characters and events of Hindu and Buddhist myths. Despite the presence of magical and mystical elements, the visual narratives teach moral lessons to the real people of the real world. The symbols signify something else beyond the represented visuals. The miniature paintings motivate the readers and viewers for reading and learning by telling interesting stories. Presentation of strange and unusual characters and events renews viewers' perception providing delight while suggesting ethical values of the society. The presentation through magical and mystical characters and actions conveys moral lessons aesthetic manner. This article traces the magical and mystical features of Nepali manuscript illuminations and attempts to throw light on their significances.